Age-specific gender differences in morphological parameters of intracranial aneurysms - Mao, Jianyao; Li, Yukui; Gao, Xin; Li, Zhangyu; Chen, Xi; Tan, Guowei; Wang, Zhanxiang; Zhong, Ping; Chen, Sifang (Frontiers in Neurology, 2025)
BackgroundGender differences are shown to exist in the incidence and outcome of subarachnoid hemorrhage as well as in the formation and progression of intracranial aneurysms. However, few studies investigated the gender difference in the morphology of intracranial aneurysms.MethodsA total of 308 consecutive patients with 346 intracranial aneurysms from 2014 to 2020 were retrospectively analyzed. Differences in 10 morphological parameters of intracranial aneurysms between males and females were compared. Continuous variables were expressed as the median [interquartile range (IQR)] and the differences were analyzed using the Mann-Whitney test. Categorical variables were expressed as numbers (frequencies) and the differences were analyzed using χ2 test. Moreover, subgroup analyses were performed according to age stratifications: ≥60 years, 50–59 years, and <50 years.ResultsThe median aspect ratio maximum [1.38, IQR (1.17–1.83) vs. 1.27, IQR (1.00–1.57)], median aspect ratio [1.29, IQR (1.00–1.76) vs. 1.18, IQR (0.93–1.54)], median bottleneck factor [1.17, IQR (1.00–1.47) vs. 1.03, IQR (0.86–1.27)], and median volume-to-ostium area ratio [5.67, IQR (2.85–9.03) vs. 3.86, IQR (1.94–7.48)] in males were significantly higher than those in females (all P < 0.01). Particularly, the differences in the above morphological parameters between genders were most prominent in patients aged ≥ 60 years, whereas no differences were found in patients aged < 50 years. There were no significant differences in other morphological parameters between males and females, including neck width, transverse, height, maximum, aneurysm volume, and height-width ratio.ConclusionsGender difference existed in the morphology of intracranial aneurysms and was affected by age. The difference was prominent in patients aged ≥ 60 years, whereas no difference was found in patients aged < 50 years.